The Perception of Ponorogo Society on Dakwah Through Social Media - Defi Firmansah; Heru Saiful Anwar (At-Ta'dib, 2020)
One of the preaching media that is becoming popular today is social media, such as Facebook, Instagram YouTube and WhatsApp. The purpose of this study was to find out how the Ponorogo community's perceptions related to the da'wah conveyed by Islamic religious leaders through social media. This research uses a qualitative approach. Data obtained through the process of interviews, observation and surveys with open questions. The interview subjects in this study were 15 people and 27 people who filled out the survey through Google Form, as additional data. The subjects are Ponorogo people who are in their ramaja age until late adulthood, that is, their active age as social media users. Research shows that the Ponorogo community is familiar with the use of social media, including WhatsApp, Instagram, FaceBook, YouTube, Line, Twitter and Podcast. This social media is widely used by the community in various activities, especially in studying the science of religion, namely by seeing da'wah through social media. The people of Ponorogo consider social media to be effective as a means of preaching for several reasons including, easy access or reach, efficient time and place, being able to choose the content or lecture content that they want to find, and not monotonous or in accordance with the times. However, social media is also considered ineffective for several reasons, including, it is feared that the content delivered by the speaker has unclear sources.